Consistency and Predictability in International Tribunals Decision on Maritime Delimitation Cases From 2009 to 2019 - Farhana, Faudzan (UI Scholars Hub, 2020)
The rules of maritime delimitation are of paramount importance in the law of the sea because coastal states will not be able to effectively exercise their legal uses of the sea without definite boundary. However, as customary law, Articles 15, 74 and 83 of UNCLOS did not provide much guidance in any particular delimitation case. Meanwhile, concluded bilateral agreements had not created enough practice of law to qualify as customary law. Thus, it is left to the international tribunals to form the delimitation rules. However, cases decided by the international tribunals show a lack of consistency in applying two main methods based on relevant provisions of UNCLOS. Both equidistance and the equitable principle has been used on plenty of occasions, as well as other criteria. This study aims to examine whether the approach of international tribunals to maritime delimitation cases has become more predictable and consistent during 2009-2019. Limited to the cases decided by the ICJ, ITLOS, and PCA, the study found that there is no significant deviation from the application of Article 15 UNCLOS within the proceedings of the cases. However, the unpredictability of the decision in the Ghana/Cote d’Ivoire case shows that the Court is more focus on the consistency of methodology than principle matter. In applying Article 74 and 83 UNCLOS, the Tribunals also put more effort into ensuring a consistent methodology. However, plenty of discretion also available for the Tribunals. Although such discretion is crucial, it needs to utilise carefully to maintain the consistency and predictability of the law. Without the consistent interpretation and predictable translation of UNCLOS from the International Tribunals, it is impossible to preserve the Law of Maritime Delimitation.